The Ghostless Garden City: Evaluating the Clean and Green Movement in Singapore - Yi Ong, Jun (Nakhara : Journal of Environmental Design and Planning, 2012)
The Garden City image of Singapore is visually projected through roadside tree-planting, parks and nature reserves. This image has been promoted by the Clean and Green Movement, which broadly refers to government policies that enforce regulations in relation to cleaning and greening. So far, literature concerning the Movement has focused on promoting the Garden City. On the contrary, this paper argues that the lack of the original sense of place through constructed greenery has lead to the Ghostless Garden City, which can also be seen as being authentic to Singapore.